Evaluation of soybean varieties for resistance to adzuki bean beetle (Collosobruchus chinenesis L.) (Coleoptera: bruchidae) by the no-choice method - Umeta, T.; Mendesil, E.; Bayissa, W.; Abebe, A.T. (Elsevier, 2026)
Soybean (Glycine max L.) is one of the primary sources of affordable protein and edible oil, globally. However, biotic and abiotic factors pose critical threats to its production both in the field and in storage. Adzuki bean beetle (Callosobruchus chinensis L.) is one of the most economically important storage insect pests of legumes, including soybeans, that cause tremendous grain damage and weight loss. However, research efforts on the evaluation of soybean varietal resistance for the management of the pest have been limited. This study was, therefore, conducted to evaluate and screen soybean-released varieties for their resistance to adzuki bean beetles. Twenty-three soybean varieties were evaluated under laboratory conditions in a no-choice experiment. The experiment was set up in an RCBD with three replications. Data collected include number of eggs laid, number of adult bruchid emergence and median development time, while Dobie's Susceptibility Index (DSI) was used to classify the varieties as resistant or susceptible. The results revealed highly significant differences (P < 0.001) among the screened soybean varieties for number of eggs, adult emergence, susceptibility index, seed damage, and weight loss. The percentage seed damage was positively and significantly correlated with percent weight loss, number of holes per total seed, number of adult bruchids emerged, and Dobie susceptibility index, but negatively and significantly correlated with median developmental periods. Dobie susceptibility index revealed that about13 % of the varieties were categorized as resistant, while 34.8 % were moderately resistant, 43.5 % susceptible, and the remaining 8.7 % highly susceptible against C. chinenesis. The varieties categorized as resistant include Gute-19, Melkobonsa, and Bilo-19, which can serve as sources of desirable genes of resistance and are expected to immensely contribute to the reduction of postharvest losses in storage due to the pest.